Prevention of musculoskeletal disorders as occupational health problem among dental professionals - Stavreva, Natasha; Bajraktarova Valjakova, Emilija; Elenchevski, Sasho; Janeva, Nadica; Tosheska Spasova, Natasha; Kokolanski, Vlatko; Mijakoski, Dragan (Македонско лекарско друштво = Macedonian medical association, 2024)
Objective: Musculoskeletal disorders (MSDs) have been identified as a significant occupational health problem among dental professionals. MSDs can be defined as any injury to the human support system, including the bones, cartilage, muscles, ligaments, tendons, blood vessels, nerves due to exposure to hazards at the workplace. For dental professionals they occur commonly in the neck, shoulder, lower back and wrists. They are significant work-related occupational health problem. Sufferers of MSDs may experience numbness, tingling, pain, decreased strength or swelling of the affected area. Ergonomics helps in designing jobs, equipment and workplaces to fit dental workers in prevention of MSD. The aims of the study are to define the significant risk factors to dental professionals’ health which lead to injuries and prevention of MSDs as occupational health problem. Material and methods: Risk factors of MSDs with specific reference to dentistry include stress, poor flexibility, improper positioning, infrequent breaks, repetitive movements, weak postural muscles, prolonged awkward postures and improper adjustment of equipment. This article includes MSDs and the signs, symptoms and risk factors and the influence of the ergonomics in prevention of these types of injuries Some authors have found symptoms of discomfort for dental workers occurred in the wrist/hands (69.5%), neck (68.5%), upper back (67.4%), low back (56.8%) and shoulders (60.0%). Results: Major health problems for dental professionals are musculoskeletal pain, especially back pain. Early symptoms of MSDs include pan, swelling, tenderness, numbness and loss of strength. Preventive measures for MSD are proper sitting posture, ergonomic equipment such as chairs, arm rests, workstation layout, dentist micro breaks, magnification systems and others. Conclusion: Ergonomic equipment, regular exercises, relaxation techniques and good scheduling assure high productivity, avoidance of illnesses and injuries and reduce the possible MSDs and increase productivity of dental professionals.
Keywords: occupational health; prevention; MSDs; dental professionals